2021
DOI: 10.1111/sltb.12791
|View full text |Cite
|
Sign up to set email alerts
|

Examining suicide assessment measures for research use: Using item response theory to optimize psychometric assessment for research on suicidal ideation in major depressive disorder

Abstract: Introduction: Progress reducing suicide death will require randomized clinical trials (RCTs) specifically targeting suicide risk. Even large RCTs may not stipulate suicide death as the primary outcome, as suicide death is relatively uncommon. Therefore, RCTs may need to specify suicidal ideation as a proxy indicator of risk. There is no consensus on the best tool for measuring suicidal ideation within RCTs. We contrasted the psychometric performance of three suicidal ideation measures to address this need. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
(41 reference statements)
1
10
0
Order By: Relevance
“…The C-SSRS is a measure used to identify and assess individuals at risk for suicide, with a special focus on ascertaining levels of recent and lifetime ideation and behavior. Evidence around its psychometric properties has been mixed ( 54 58 ). Twelve studies located in the current review tested or implemented a version of the Columbia Suicide Severity Rating Scale (C-SSRS).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C-SSRS is a measure used to identify and assess individuals at risk for suicide, with a special focus on ascertaining levels of recent and lifetime ideation and behavior. Evidence around its psychometric properties has been mixed ( 54 58 ). Twelve studies located in the current review tested or implemented a version of the Columbia Suicide Severity Rating Scale (C-SSRS).…”
Section: Resultsmentioning
confidence: 99%
“…The C-SSRS is a measure used to identify and assess individuals at risk for suicide, with a special focus on ascertaining levels of recent and lifetime ideation and behavior. Evidence around its psychometric properties has been mixed (54)(55)(56)(57)(58) (31)] is up to seven items in length. Patients are asked in the past month "have you wished you were dead or wished you could go to sleep and not wake up" (Yes/No) or "actually had any thoughts of killing yourself?"…”
Section: Columbia-suicide Severity Rating Scale (Cssrs)mentioning
confidence: 99%
“…Regarding the SI assessment, we relied on SSI measure because it is part of the clinical evaluation and management of inpatients in the mood disorder unit. Recently, McCall et al (2021) showed that the most common disagreement of dichotomized SI evaluation occurred when SSI was administered compared to other two measures. However, the authors stated that all measures available were equally able to identify low and high levels of SI, and the choice of the SI instrument may be related to time and contextual variables.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the Columbia-Suicide Severity Rating Scale (C-SSRS) is considered a gold standard for the clinical field ( 10 , 11 ). However, the gold standard for suicide research remains unclear ( 12 ).…”
Section: Introductionmentioning
confidence: 99%